Postbuckling of thick FGM cylindrical panels with tangential edge constraints and temperature dependent properties - Tung, Hoang Van (Vietnam Journal of Mechanics, 2016)
This paper investigates postbuckling behavior of thick  FGM cylindrical panels resting on elastic foundations and subjected to  thermal, mechanical and thermomechanical loading conditions. Material  properties are assumed to be temperature dependent, and graded in the  thickness direction according to a simple power law distribution in terms of  the volume fractions of constituents. Governing equations are based on  higher order shear deformation shell theory incorporating von Karman-Donnell  geometrical nonlinearity, initial geometrical imperfection, tangential edge  constraints and Pasternak type elastic foundations. Approximate solutions  are assumed to satisfy simply supported boundary conditions and Galerkin  procedure is applied to derive expressions of buckling loads and  load-deflection relations. In thermal postbuckling analysis, an iteration  algorithm is employed to determine critical buckling temperatures and  postbuckling temperature-deflection equilibrium paths. The separate and  simultaneous effects of tangential edge restraints, elastic foundations and  temperature dependence of material properties on the buckling and  postbuckling responses of higher order shear deformable FGM cylindrical  panels are analyzed and discussed.